2002
DOI: 10.1136/bjo.86.11.1269
|View full text |Cite
|
Sign up to set email alerts
|

Macular hole and myopic refraction

Abstract: Aim: To study a correlation between age at the onset and myopic refraction and axial length in patients with idiopathic macular hole and to evaluate a correlation of the size and surgical outcome of macular hole with axial length. Methods: In a prospective clinical study, 94 eyes of 91 patients with stage III and IV idiopathic macular hole were enrolled. A standardised surgical protocol was performed using vitrectomy and gas tamponade. This study evaluated the size of macular hole and the rate of anatomical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
(36 reference statements)
1
39
2
Order By: Relevance
“…This agrees with previous studies that have demonstrated specific pathological features involving the macular area in subjects with higher degrees of myopia. 12,13 It is also noted that there is a trend for thickening at the fovea in high myopia but there seem to be individual variations and the result is not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with previous studies that have demonstrated specific pathological features involving the macular area in subjects with higher degrees of myopia. 12,13 It is also noted that there is a trend for thickening at the fovea in high myopia but there seem to be individual variations and the result is not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…10 High myopes also tend to have chorioretinal atrophy at the posterior pole, 10 choroidal neovascularisation at the macular area 12 and a macular hole at the posterior pole. 13 Of late, the retinal changes in increasing degrees of myopia have been studied with the technique of optical coherence tomography (OCT). The outer macula (perifovea) has been demonstrated using OCT to be thinner in myopes.…”
mentioning
confidence: 99%
“…In a case series of high myopia with macular hole, García-Arumí et al [5] reported an 87.5% primary anatomical closure rate after operation, while Patel et al reported a rate of only 60% with a single operation in highly myopic eyes [6]. Case-control studies by Sulkes et al., Kobayashi et al, and Kwok et al did not reveal significant differences in macular hole closure rates between highly myopic and non-highly myopic eyes [7][8][9]. However, they all used biomicroscopy alone to evaluate the results and defined only flattening of the edges or resolution of cuff of subretinal fluid as surgical success [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 92%
“…18 The elevated foveola and fovea area in young, healthy highly myopic eyes might explain the high incidence of macular hole, which may be associated with retinal detachment, myopic traction maculopathy, and foveoschisis. 10,11,[19][20][21][22][23] Figure 2 OCT scans of the macula (both eyes) in normal eyes (a) and highly myopic eyes (b) including the colour scale and scan schematic. The foveola and fovea (1 mm) were thicker but the inner macular area (3 mm) and outer macular area (6 mm) were thinner in highly myopic eyes.…”
Section: Discussionmentioning
confidence: 99%